2009
DOI: 10.1111/j.1365-2222.2008.03163.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oxidative stress‐related biomarkers and antioxidant status with asthma and atopy in young adults: a population‐based study

Abstract: The levels of oxidative stress-related biomarkers and antioxidant status in plasma may not be related to asthma in the general population in the absence of more severe symptoms or exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Furthermore, association with advanced duration and stage of COPD has been reported [34]. Serum UA levels were not significantly associated with lung function and symptoms in patients with asthma [35].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, association with advanced duration and stage of COPD has been reported [34]. Serum UA levels were not significantly associated with lung function and symptoms in patients with asthma [35].…”
Section: Discussionmentioning
confidence: 99%
“…Exhaled breath condensate and broncho-alveolar lavage samples from affected individuals have been shown to contain increased levels of 8-isoprostane, and other well established maker of oxidative stress 113, 114 . Peripherally, additional biomarkers of oxidative stress (superoxide anion generation, lipid peroxidation, total nitrates/nitrites, total protein carbonyls, and total protein sulfhydrils) may be increased, concomitant with decreased levels of specific anti-oxidants (superoxide dismutase, catalase activity, glutathione, and glutathione peroxidase activity, etc) 112, 115, 116 . It remains unclear if increased levels of oxidative stress observed in asthmatic individuals is a cause of disease, or rather a result of ongoing inflammation in the airways, which itself produces reactive oxygen species.…”
Section: Non-immunologic Mechanismsmentioning
confidence: 99%
“…That study demonstrated that there was no relationship between plasma UA and lung function 12. However, these relationships were only investigated in a population of young adults, and the association between sUA levels and pulmonary function in the general population remains to be elucidated.…”
Section: Introductionmentioning
confidence: 96%